A Novel Near-Infrared Tricyanofuran-Based Fluorophore Probe for Polarity Detection and LD Imaging - Zhaojia Hang; Shengmeng Jiang; Zhitong Wu; Jin Gong; Lizhi Zhang (Molecules)
In this paper, LD-TCF, a targeting probe for lipid droplets (LDs) with a near-infrared emission wavelength and large Stokes shift, was fabricated for polarity detection by assembling a donor–π–acceptor (D–π–A) molecule with typical twisted intramolecular charge transfer (TICT) characteristics. Surprisingly, the fluorescence emission wavelength of the newly constructed probe LD-TCF was stretched to 703 nm, and the Stokes shift was amplified to 126 nm. Furthermore, LD-TCF could specifically answer the change in polarity efficiently and did not experience interference from other biologically active materials. Importantly, LD-TCF exhibited the ability to target lipid droplets, providing valuable insights for the early diagnosis and tracking of pathophysiological processes underlying LD polarity.